Sexual health service adaptations to the coronavirus disease 2019 (COVID‐19) pandemic in Australia: a nationwide online survey. (2nd September 2021) - Phillips, Tiffany R.; Fairley, Christopher K.; Donovan, Basil; Ong, Jason J.; McNulty, Anna; Marshall, Lewis; Templeton, David J.; Owen, Louise; Ward, Alison; Gunathilake, Manoji; Russell, Darren; Langton‐Lockton, Julian; et al.
Abstract: Objective : Examine the changes in service delivery Australian public sexual health clinics made to remain open during lockdown. Methods : A cross‐sectional survey designed and delivered on Qualtrics was emailed to 21 directors of public sexual health clinics across Australia from July‐August 2020 and asked about a variety of changes to service delivery. Descriptive statistics were calculated. Results : Twenty clinics participated, all remained open and reported service changes, including suspension of walk‐in services in eight clinics. Some clinics stopped offering asymptomatic screening for varying patient populations. Most clinics transitioned to a mix of telehealth and face‐to‐face consultations. Nineteen clinics reported delays in testing and 13 reported limitations in testing. Most clinics changed to phone consultations for HIV medication refills (n=15) and eleven clinics prescribed longer repeat prescriptions. Fourteen clinics had staff redeployed to assist the COVID‐19 response. Conclusion : Public sexual health clinics pivoted service delivery to reduce risk of COVID‐19 transmission in clinical settings, managed staffing reductions and delays in molecular testing, and maintained a focus on urgent and symptomatic STI presentations and those at higher risk of HIV/STI acquisition. Implications for public health : Further research is warranted to understand what impact reduced asymptomatic screening may have had on community STI transmission.